The factors influencing working Gen Z intentions to purchase green cosmetics products in Malaysia - Mohd Tan, Athirah; Sevam, Vishu; Mangkau, Ivy Deirdre (Research and Scientific Innovation Society, 2025)
The rising demand for green and sustainable products has positioned green cosmetics as a growing segment of the Malaysian beauty industry. Despite increasing awareness, purchase intentions toward green cosmetics among working generation Z remain inconsistent and underexplored compared to student populations. Therefore, the research aims to examine the influence of attitude, subjective norm, perceived behavioral control an environmental concern on working Gen Z’s intentions to purchase green cosmetics in Malaysia. A quantitative, cross-sectional survey design was distributed, targeting 120 working Gen Z respondents selected through purposive sampling. Data were collected using an online structured questionnaire and analyzed through SPSS, incorporating descriptive statistics, reliability tests, normality checks and spearman’s rank order correlation. The results revealed that all four independent variables, attitude (r = 0.647, p < 0.01), subjective norm (r = 0.657, p < 0.01), perceived behavior control (r = 0.757, p < 0.01) and environmental concern (r = 0.657, p < 0.01) showed strong and positive correlations with purchase intentions. These findings indicate that working Gen Z consumers are more likely to adopt green cosmetics when they hold favorable attitudes, experience positive social influence, feel confident in their purchasing ability, possess strong environmental values. Academically, this research contributes by extending the theory of Planned Behavior (TPB) to a working Gen Z context, which has been less examined in previous research. From an industry perspective, the results provide practical guidance for cosmetic brands to strengthen green marketing strategies by enhancing eco-friendly branding, social engagement, affordability and accessibility. By addressing these key factors, businesses can effectively encourage sustainable purchasing behavior and build long term loyalty among Malaysia’s working Generation Z consumers.